PENGARUH DIFERENSIASI KUALITAS AUDIT DAN KESULITAN KEUANGAN PERUSAHAAN TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK - YULIA SYAFITRI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. This research aimed to obtain empirical evidence of the differentiation of audit quality, financial distress and audit opinion to audit switching. This research was using samples of manufacturing industry. The companies were listed on The Indonesian Stock Exchange in 2011-20151. Based on method purposive sampling, research samples total are 175 financial statements. Hypothesis in this research used logistic regression 19. This research indicated that financial distress had significant influencing on the audit switching. Financial distress had significant value 0.007 below 0.05. The differentiation of audit quality did not have significant a value is 0,392 larger than 0,05. The result is the differentiation of audit quality did not have significant influencing on the audit switching. Future studies may consider using the research object of all companies listed on the Stock Exchange, so that it can be seen as a valid generalization theory. Measurement of the variables in the differentiation of audit quality further research should be more accurate, not only see from displacement class or reputation KAP Brand Name undertaken by the clients of the Big Four.